Development and testing of bio-based amphiphilic-designed polymer coatings as a safer approach to marine biofouling - Sara Pandolfi; Alessandro Piazza; Marina Antonia Colangelo; Martina Franchini; Franca Guerrini; Martina La Torre; Patrizio Raffa; Federica Spina; Giovanna Cristina Varese; Francesco Venice; Chiara Samorì; Federica Costantini (Marine Pollution Bulletin, 2026)

A review on PFAS mitigation in wastewater: integrating removal technologies, challenges and innovative solutions - Ilenia Farina; Antonella Scotto di Uccio; Alessandro Moretti; Francesco Colangelo (Reviews in Environmental Science and Bio/Technology, 2026)

Corrigendum to “A survey of VKORC1 missense mutations in eleven Italian islands reveals widespread rodenticide resistance in house mice” [Sci. Total Environ. 953 (2024) 176090] - Francesco Gallozzi; Lorenzo Attili; Paolo Colangelo; Davide Giuliani; Dario Capizzi; Paolo Sposimo; Filippo Dell'Agnello; Rita Lorenzini; Emanuela Solano; Riccardo Castiglia (Science of The Total Environment, 2025)

New genetic data suggest ancient colonization of southern Italian islands by the western European house mouse Mus musculus domesticus - Francesco Gallozzi; Lorenzo Attili; Emanuela Solano; Paolo Colangelo; Riccardo Castiglia (Mammal Research, 2025)

Earlywood vessel characteristics are early indicators of drought-induced decline in ring-porous oak species within the Mediterranean Basin - Michele Colangelo; Antonio Gazol; J. Julio Camarero; Marco Borghetti; Raúl Sánchez-Salguero; Luis Matias; Maria Castellaneta; Paola Nola; Francesco Ripullone (Science of The Total Environment, 2025)

A survey of VKORC1 missense mutations in eleven Italian islands reveals widespread rodenticide resistance in house mice - Francesco Gallozzi; Lorenzo Attili; Paolo Colangelo; Davide Giuliani; Dario Capizzi; Paolo Sposimo; Filippo Dell'Agnello; Rita Lorenzini; Emanuela Solano; Riccardo Castiglia (Science of The Total Environment, 2024)

Drought legacies in mixed Mediterranean forests: Analysing the effects of structural overshoot, functional traits and site factors - Santain S.P. Italiano; J. Julio Camarero; Marco Borghetti; Michele Colangelo; Angelo Rita; Francesco Ripullone (Science of The Total Environment, 2024)

Radial growth, wood anatomical traits and remote sensing indexes reflect different impacts of drought on Mediterranean forests - Santain S.P. Italiano; J. Julio Camarero; Marco Borghetti; Michele Colangelo; Manuel Pizarro; Francesco Ripullone (Forest Ecology and Management, 2023)

Integrative taxonomy approach to detect spatial and temporal variability of the Mediterranean benthic communities through artificial substrate units (ASUs) - Francesco Mugnai; Barbara Mikac; Marina Antonia Colangelo; Kenan Oguz Matterson; Marco Abbiati; Federica Costantini (Frontiers in Marine Science, 2023)
Monitoring spatial and temporal changes of marine benthic communities using standardized procedures is essential to take necessary steps towards conservation of marine ecosystems. In this study we combined Artificial Substrate Units (ASUs) for sampling of benthic communities, with integrative taxonomy approach that incorporated morphological identification of organisms and COI DNA metabarcoding, to characterize the diversity of communities at three locations across the Central Mediterranean Sea (Livorno and Palinuro, Italy; Rovinj, Croatia) in 2019 and 2020. Significant differences in the communities’ structure were observed both at large spatial scale between sampled locations, and at small spatial scale (less than ten kilometers) between sites. Moreover, significant temporal variability in species richness and structure of benthic assemblages was detected, with higher richness in 2020. Revealed variability can probably be attributed to the peculiar geomorphological, oceanographical, and ecological features of locations, but also to the influence of interplaying local chemical and physical factors and biological processes such as species settlement, competition, and migration that can act at small spatial and temporal scales. The similarity in the species composition and community structure accessed by morphological and metabarcoding approaches was low, with only 16% of the species (out of 133 species identified overall) commonly detected by both approaches. This is mostly both due to a lack of data on COI sequences of numerous benthic invertebrates in the public barcoding databases on the one hand, and difficulties in detecting small and cryptic taxa through morphological analyses on the other. This suggests that combining of two approaches is required to fully describe the biodiversity of benthic assemblages. Finally, comparison of the spatial variability of the benthic communities’ structure with two approaches at different taxonomic levels, indicated that genus and family levels give results that are consistent to those obtained by the species level. This suggests that family level might be satisfactory in monitoring the spatial-temporal variability of Mediterranean hard bottom benthic communities.

Assessment of carbon emissions’ effects on the investments in conventional and innovative waste-to-energy treatments - Gianpiero Colangelo; Francesco Facchini; Luigi Ranieri; Giuseppe Starace; Micaela Vitti (Journal of Cleaner Production, 2023)

Tree-ring and remote sensing analyses uncover the role played by elevation on European beech sensitivity to late spring frost - Enrico Tonelli; Alessandro Vitali; Francesco Malandra; J. Julio Camarero; Michele Colangelo; Angelo Nolè; Francesco Ripullone; Marco Carrer; Carlo Urbinati (Science of The Total Environment, 2023)

Production and characterization of lightweight aggregates from municipal solid waste incineration fly-ash through single- and double-step pelletization process - Alberto Ferraro; Vilma Ducman; Francesco Colangelo; Lidija Korat; Danilo Spasiano; Ilenia Farina (Journal of Cleaner Production, 2023)

Species specific vulnerability to increased drought in temperate and Mediterranean floodplain forests - Osvaldo Pericolo; J. Julio Camarero; Michele Colangelo; Cristina Valeriano; Raúl Sánchez-Salguero; Marco Borghetti; Maria Castellaneta; Paola Nola; Francesco Ripullone (Agricultural and Forest Meteorology, 2023)

Cold-bonding process for treatment and reuse of waste materials: Technical designs and applications of pelletized products - Alberto Ferraro; Francesco Colangelo; Ilenia Farina; Marco Race; Raffaele Cioffi; Christopher Cheeseman; Massimiliano Fabbricino (Critical Reviews in Environmental Science and Technology, 2021)

Evaluating growth and intrinsic water-use efficiency in hardwood and conifer mixed plantations - Tiziana Gentilesca; Giovanna Battipaglia; Marco Borghetti; Michele Colangelo; Simona Altieri; Agostino M. S. Ferrara; Antonio Lapolla; Angelo Rita; Francesco Ripullone (Trees, 2021)
Key message Juglans, Fraxinus, Quercus and Pinus species seem to better maximize the carbon–water ratio providing useful indications on species selection for forestry plantations in areas with increasing drought risk. Abstract Maximizing carbon sequestration for a given water budget is extremely important in the contest of climate change in the Mediterranean region, which is characterized by increasing temperatures and rising water stress. This issue is fundamental for plantation stands, where limited water availability during the growing season reduces CO 2 assimilation and, consequently, tree growth. In this study, the main objective was to investigate the performances in terms of carbon–water balance of conifer ( Pinus halepensis and Cupressus semperviren s) and hardwood ( Quercus robur, Juglans regia, Fraxinus excelsior and Populus spp.) mixed plantations. To this aim, we used carbon isotope signatures to evaluate the intrinsic water-use efficiency ( iWUE) and the species-specific relationship between basal area increments ( BAI ) and iWUE . At the species level, the highest iWUE values corresponded to the lowest carbon accumulation in terms of BAI, for water-saving species such as Cupressus . Conversely, Populus had the lowest iWUE and the highest BAI accumulation. Juglans, Fraxinus, and Pinus showed the most balanced ratio between BAI and iWUE . Overall, no clear correlation of iWUE and BAI was evident within all species, except for Populus and Cupressus. Considering projected aridification and increased temperatures that will negatively impact the growth, our data suggest that Pinus, for conifers, and Quercus, Juglans, Fraxinus for hardwood species should be preferred when choosing species for forestry plantation, as they performed better in terms of BAI and iWUE ratio.

Comparative LCA of concrete with recycled aggregates: a circular economy mindset in Europe - Francesco Colangelo; Tomás Gómez Navarro; Ilenia Farina; Antonella Petrillo (The International Journal of Life Cycle Assessment, 2020)

Correction: Xylem Functional Traits as Indicators of Health in Mediterranean Forests - Marco Borghetti; Tiziana Gentilesca; Michele Colangelo; Francesco Ripullone; Angelo Rita (Current Forestry Reports, 2020)

Xylem Functional Traits as Indicators of Health in Mediterranean Forests - Marco Borghetti; Tiziana Gentilesca; Michele Colangelo; Francesco Ripullone; Angelo Rita (Current Forestry Reports, 2020)
Purpose of Review We conducted a literature survey and meta-analysis to assess, in Mediterranean forests impacted by drought, the role of xylem functional traits as indicators of tree health, and their potential to adjust over a range of climatic conditions to support tree performance and survival. We aimed also to depict the geographic variability of xylem functional traits among Mediterranean forest trees as a tool for regional scale-oriented vulnerability assessment. Recent Findings Associations were investigated among xylem functional traits, hydraulic safety, and whole plant drought resistance for tree species in Mediterranean-type climates. Variable data were available from a number of study cases of Mediterranean forest communities impacted by intense drought, wherein tree growth and xylem functional traits were investigated along with tree decline and dieback episodes. Variable data were available from a number of studies that analyzed xylem trait adjustments to climatic conditions at different temporal scales. Summary We observed differing growth patterns and xylem conduit area responses in healthy and unhealthy trees and we sketched hydraulic strategies that may fit observed patterns. Overall, a clear role of xylem conduit size as stand-alone tree health indicator did not emerge. We showed that xylem traits may adjust along different temporal scales and may support the performance and health of Mediterranean tree species over a range of climatic conditions. We outlined substantial geographic variability in xylem traits across the Mediterranean region, suggesting patchy responses to increasing drought. Knowledge gaps and needed lines of research are highlighted.

Pre-treatments of MSWI fly-ashes: a comprehensive review to determine optimal conditions for their reuse and/or environmentally sustainable disposal - Alberto Ferraro; Ilenia Farina; Marco Race; Francesco Colangelo; Raffaele Cioffi; Massimiliano Fabbricino (Reviews in Environmental Science and Bio/Technology, 2019)

Phenotypic Changes Across a Geographic Gradient: The Case of Three Sympatric Dolphin Species - Giulia Guidarelli; Paolo Colangelo; Maria Carla de Francesco; Paola Nicolosi; Carlo Meloro; Anna Loy (Evolutionary Biology, 2018)

Purinergic Modulation of Spinal Neuroglial Maladaptive Plasticity Following Peripheral Nerve Injury - Giovanni Cirillo; Anna Maria Colangelo; Miluscia Berbenni; Vita Maria Ippolito; Ciro De Luca; Francesco Verdesca; Leonilde Savarese; Lilia Alberghina; Nicola Maggio; Michele Papa (Molecular Neurobiology, 2015)